4 Minutes Rule in Perimortem Caesarean Delivery: Does it Still Relevant? Case Series (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: perimortem caesarean delivery; resuscitative hysterotomy; maternal cardiac arrest